CAREER INTELLIGENCE : THE 12 NEW RULES FOR WORK AND LIFE SUCCESS - MOSES, Barbara (Berrett-Koehler Pub. San FranciscoUS, 1998)
Seeks to assist readers to respond effectively to changes both at work and at home. Provides the information and skills needed for coping in the transformed workplace. Deals with matters such as: generational issues; self-marketing in the workplace and, career independence for staff members. The twelve rules include: ensure your marketability; think globally; and keep on learning.